Molecular Transition of an Adult Low-Grade Brain Tumor to an Atypical Teratoid/Rhabdoid Tumor Over a Time-Course of 14 Years. Issue 8 (14th July 2017) - Schweizer, Yvonne; Meszaros, Zsolt; Jones, David T.W.; Koelsche, Christian; Boudalil, Miream; Fiesel, Petra; Schrimpf, Daniel; Piro, Rosario M.; Brehmer, Stefanie; von Deimling, Andreas; Kerl, Ulrich; Seiz-Rosenhagen, Marcel; et al.
Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) of the central nervous system is a highly malignant, pediatric brain tumor typically arising de novo. Inactivation of SMARCB1 is a defining molecular event. We present here a rare case of an adult (35 years) low-grade SMARCB1 -deleted brain tumor with transition into prototypical AT/RT over 14 years. Molecular analysis was performed for 3 tumor presentations including copy number analysis, DNA methylation analysis (450k), and whole exome sequencing. We detected the identical somatic SMARCB1 deletion at all 3 time-points. In an unsupervised hierarchical clustering of methylation data together with 127 reference cases comprising 9 brain tumor classes all 3 manifestations clustered with AT/RT. Exome sequencing revealed an increase of mutational burden over time. The acquired mutations and additional copy number changes did not affect known cancer genes. In conclusion, we demonstrate molecular changes associated with histological and clinical transition of a low-grade brain tumor to an adult AT/RT. Our observation of a stable disease course for nearly 10 years in a tumor with SMARCB1 loss and an AT/RT-like DNA methylation profile indicates that caution may be required in the diagnostic interpretation of such findings in adult patients.